Seismic Anisotropy Within an Active Fluid Flow Structure: Scanner Pockmark, North Sea - Bayrakci, G.; Callow, B.; Bull, J. M.; Minshull, T. A.; Provenzano, G.; North, L. J.; Macdonald, C.; Robinson, A. H.; Henstock, T.; Chapman, M. (Frontiers in Earth Science, 2021)
Understanding sub-seabed fluid flow mechanisms is important for determining their significance for ocean chemistry and to define fluid pathways above sub-seafloor CO2 storage reservoirs. Many active seabed fluid flow structures are associated with seismic chimneys or pipes, but the processes linking structures at depth with the seabed are poorly understood. We use seismic anisotropy techniques applied to ocean bottom seismometer (OBS) data, together with seismic reflection profiles and core data, to determine the nature of fluid pathways in the top tens of metres of marine sediments beneath the Scanner pockmark in the North Sea. The Scanner pockmark is 22 m deep, 900 x 450 m wide and is actively venting methane. It lies above a chimney imaged on seismic reflection data down to ~1 km depth. We investigate azimuthal anisotropy within the Scanner pockmark and at a nearby reference site in relatively undisturbed sediments, using the PS converted (C-) waves from a GI gun source, recorded by the OBS network. Shear-wave splitting is observed on an OBS located within the pockmark, and on another OBS nearby, whereas no such splitting is observed on 23 other instruments, positioned both around the pockmark, and at an undisturbed reference site. The OBSs that show anisotropy have radial and transverse components imaging a shallow phase (55 - 65 ms after the seabed) consistent with PS conversion at 4 to 5 m depth. Azimuth stacks of the transverse component show amplitude nulls at 70° and 160° N, marking the symmetry axes of anisotropy and indicating potential fracture orientations. Hydraulic connection with underlying, over pressured gas charged sediment has caused gas conduits to open, either perpendicular to the regional minimum horizontal stress at 150-160o N or aligned with a local stress gradient at 50-60° N. This study reports the first observation of very shallow anisotropy associated with active methane venting.